Modeling of micro-diaphragm for optical pressure sensor for human artery pulse wave detection / Khairunnisa Hasikin - Khairunnisa , Hasikin (2010)
This thesis presents the development of a micro-diaphragm for an optical pulse pressure sensor using Micro-electro-mechanical Systems (MEMS) technology. Modelling of the micro-diaphragm was conducted and the comparison of its performance was simulated for silicon nitride and polyirnide materials. In addition. diaphragm's radius and thickness were varied to further analyze the performance of the micro-diaphragm. There are three design parameters that affecting the micro-diaphragm performance namely diaphragms radius. thickness and material. Thus, an optimization analysis using Taguchi method was done to attain significant design parameters that give the best micro-diaphragm performance. Findings indicated that the best performance of the micro-diaphragm was obtained when the micro-diaphragm achieved high deflection and sensitivity as well as low resonance frequency. Simulation results have concluded that these performances are achieved when the diaphragm's radius and thickness are large and small respectively. Furthermore, the Taguchi method verified that the optimized design parameters radius of 90~-tm, thickness of 4~-tm and polyimide material have successfully achieved the best micro-diaphragm performance. In addition, the selected design parameters have been proven to provide an adequate sensitivity to detect the pulse pressure on human's radial artery.